ANALISIS PENGARUH DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN (STUDI PADA WISATAWAN KEBUN BINATANG GEMBIRALOKA ZOO YOGYAKARTA) - Wardani, Niken Retno; Fitriani, Dyah (Universitas Ahmad Dahlan, 2017)
This study aims to analyze the influence of tourist attraction on tourist visiting decisions (study of zoo tourists Gembiraloka Zoo Yogyakarta), both partially and simultaneously. Population in this study are visitors who visit Gembiraloka Zoo Yogyakarta. Samples taken were 60 respondents with the sampling technique using Non Probability Sampling with Purposive Sampling. Types of data are primary data and techniques data collection using a questionnaire that has been tested first with validity and reliability tests. Data analysis method used is quantitative analysis using multiple linear regression, t test, and F test coefficient of determination (R2). Based on the results of data analysis with SPSS program statistical tools 20, it can be concluded that the price variable (X1) has a significant effect on decision to visit tourists with a sign value of 0.018. Place (X2) no significant effect on the decision of visiting tourists with the sign value is 0.089. Product (X3) has a significant effect on decisions visiting tourists with a sign value of 0.033. Employees (X4) are influential significant to tourists visiting decisions with a sign value of 0.019. Simultaneously the price, place, product, and employee have a significant effect to the decision to visit tourists with a sign value of 0,000 Coefficient the resulting determination of 0723 which means that at 72.3% the decision to visit the Gembiraloka Zoo in Yogyakarta is influenced by all four variables are used, and the rest are influenced by other variables.